Wind tunnel study on convective heat transfer performance of vegetation canopies with different structures. (September 2022) - Yan, Junru; Zhao, Lihua; Zhang, Yu; Zhang, Lei
Abstract: Turbulent airflow around urban vegetation significantly affects transpiration cooling, pollutant dispersion, insect habitat, outdoor thermal environment, and building energy consumption. A major challenge is investigating the effect of different vegetation canopies on turbulent transfer and improving the calculation of the canopy convective heat transfer coefficients ( h c ) using canopy structural parameters. To address this challenge, we conducted 744 experiments using an adjustable artificial vegetation canopy and assessed different canopy structures and wind speeds and the presence/absence of obstacles. The results showed that the h c was not significantly affected by the relative angle between the leaves at a constant leaf windward angle. The largest h c occurred at a leaf windward angle ( θ ) of 24° and a windward leaf area index ( L A I w ) of 1.1. The proposed semi-mechanical and empirical models showed good prediction accuracy ( R a d 2 = 0.93). Moreover, the predictability of canopy turbulent transfer, vegetation energy budgets, and thermal comfort was enhanced by incorporating the h c model into urban microclimatic models (UMMs). Future applications and development of this model will facilitate wind-sensitive urban planning and help provide guidelines for landscape management to mitigate insect problems and improve building ventilation. Highlights: The h c was not significantly affected by the relative angle between leaves. The maximum h c at a leaf windward angle of 24° and an LAI of 1.1. A wind tunnel experiment method for the h c is proposed. Plant selection and pruning strategies are provided.